Constraints on the exploitation of the functional properties of objects in expert tool-using chimpanzees (Pan troglodytes). (September 2016) - Povinelli, Daniel J.; Frey, Scott H.
Abstract: Many species exploit immediately apparent dimensions of objects during tool use and manufacture and operate over internal perceptual representations of objects (they move and reorient objects in space, have rules of operation to deform or modify objects, etc). Humans, however, actively test for functionally relevant object properties before such operations begin, even when no previous percepts of a particular object's qualities in the domain have been established. We hypothesize that such prospective diagnostic interventions are a human specialization of cognitive function that has been entirely overlooked in the neuropsychological literature. We presented chimpanzees with visually identical rakes: one was functional for retrieving a food reward; the other was non-functional (its base was spring-loaded). Initially, they learned that only the functional tool could retrieve a distant reward. In test 1, we explored if they would manually test for the rakes' rigidity during tool selection, but before using it. We found no evidence of such behavior. In test 2, we obliged the apes to deform the non-functional tool's base before using it, in order to evaluate whether this would cause them to switch rakes. It did not. Tests 3–6 attempted to focus the apes' attention on the functionally relevant property (rigidity). Although one ape eventually learned to abandon the non-functional rake before using it, she still did not attempt to test the rakes for rigidity prior to use. While these results underscore the ability of chimpanzees to use novel tools, at the same time they point toward a fundamental (and heretofore unexplored) difference in causal reasoning between humans and apes. We propose that this behavioral difference reflects a human specialization in how object properties are represented, which could have contributed significantly to the evolution of our technological culture. We discuss developing a new line of evolutionarily motivated neuropsychological research on action disorders.